Platelets, lymphocytes and erythrocytes from Alzheimer’s disease patients: the quest for blood cell-based biomarkers - Pluta, Ryszard; Ułamek-Kozioł, Marzena; Januszewski, Sławomir; Czuczwar, Stanisław (Folia Neuropathologica, 2018)
In elderly population, Alzheimer’s disease is a common neurodegenerative disorder and accounts for about 70% of all cases of dementia. The neurodegenerative processes of this disease start presumably 20 years ahead of the clinical beginning of the disorder. The postmortem histopathological examination, brains from Alzheimer’s disease patients with characteristic features like amyloid plaques and neurofibrillary tangles, neuronal and synaptic disintegration confirm the final diagnosis of Alzheimer’s disease. Senile plaques are composed of -amyloid peptide, deriving from the amyloid protein precursor, which is present not only in the brain tissue, but also in other non-neuronal tissues. Some investigations reported that platelets possess amyloid protein precursor and all the enzymatic activities required for the metabolism of this protein throughout the same pathways present in the brain. Thus, platelets may be a good peripheral blood cell-based biomarker to study the onset of Alzheimer’s disease. Another line of research indicated molecular and cellular aberrations in blood lymphocytes and erythrocytes from Alzheimer’s disease patients and emphasizes the systemic nature of the disease. In this review, we will summarize the recent knowledge on the involvement and/or response of platelets, lymphocytes and red blood cells in the circulation during Alzheimer’s disease development. The facts will be reviewed with the special possibility for applying the above blood cells as Alzheimer’s disease preclinical and antemortem blood cell-based biomarkers.